The differentiation of metonymy and metaphor concepts in modern linguistics (Revista de Investigaciones Universidad del Quindío, 2022)
The article is devoted to the feasibility of distinction between metonymy and metaphor; since ancient times, language researchers have studied them together because they are based on the transfer of names by similarity or analogy of features. The main task of the article is to outline the dominant theories of metonymy and metaphor, developed in the plane of the semantic-syntactic paradigm, as well as to present cognitively oriented considerations about the essence of these two phenomena, which prove their distinction. Based on the basic postulates of cognitive linguistics, particularly the theory of conceptual metaphor, the theory of mental spaces, and the theory of conceptual integration, the authors prove a significant difference between the two outlined linguocognitive mechanisms. Based on phraseological units of modern French, the authors prove, first, that metonymy represents a real adjacency of concepts, while metaphor - hypothetical. Secondly, their difference lies in the different number of conceptual spheres involved in metonymization (one conceptosphere) and metaphorization (more than two conceptospheres). Thirdly, in metaphorization, projected images reflect various (sometimes unexpected) associations that link different spheres of GOAL and SOURCE, while in metonymization, projected images adhere to logically established connections.
Keywords: metaphor; metonymy; similarity of concepts; cognitive semantics; conceptual sphere